2018
DOI: 10.1021/acsnano.7b09095
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Lipid Extraction from Membranes by Boron Nitride Nanosheets

Abstract: Two-dimensional (2D) materials can mechanically insert into cell membranes and extract lipids out, thus leading to the destruction of cell integrity. On the one hand, the cytotoxicity of 2D materials can be harnessed in surface engineering to resist biofouling, and on the other hand, it causes great concern with in vivo biomedical applications ranging from drug delivery to nanoimaging. To understand the nature of this cytotoxic behavior and find strategies to control it, we performed molecular dynamics (MD) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…It is interesting to note that a recent mechanism study by Fan and coworkers showed that the lipid extraction from cell membranes by BN nanosheets is temperature dependent: the lipid extraction behavior can emerge at higher temperatures due to a phase transition occurring in the lipid membrane, thereby inducing the cytotoxicity of the nanosheets . Herein, we also examined whether this temperature‐dependent lipid extraction behavior is also present in the case of C 2 N. A set of additional three independent simulations based on the initial system of C 2 N–POPC extraction simulations were performed at a higher temperature 310 K with each running for 300 ns.…”
Section: Resultsmentioning
confidence: 96%
“…It is interesting to note that a recent mechanism study by Fan and coworkers showed that the lipid extraction from cell membranes by BN nanosheets is temperature dependent: the lipid extraction behavior can emerge at higher temperatures due to a phase transition occurring in the lipid membrane, thereby inducing the cytotoxicity of the nanosheets . Herein, we also examined whether this temperature‐dependent lipid extraction behavior is also present in the case of C 2 N. A set of additional three independent simulations based on the initial system of C 2 N–POPC extraction simulations were performed at a higher temperature 310 K with each running for 300 ns.…”
Section: Resultsmentioning
confidence: 96%
“…h-BN is an attractive 2D material for membrane applications owing to its unique and excellent properties such as high strength, insulation, thermal stability and conductivity and chemical inertness [111][112][113]. Those properties make it promising, but its extremely high chemical inertness has restricted its wide-spread application.…”
Section: Surface Functionalization Of H-bnmentioning
confidence: 99%
“…To avoid the effect of sharp edges and corners of nanosheets as reported previously, rounded nanosheet models with smooth edges were used. In previous simulation studies, the size of nanosheet models was usually comparable with membrane thickness (several nanometers) . However, nanosheets in experiments are much larger, and the size of nanosheets can be several hundreds (and even thousands) of nanometers .…”
Section: Resultsmentioning
confidence: 96%
“…First, lipids in the liposome are extracted out under van der Waals attraction and hydrophobic interaction as reported by Tu et al Then, the climbing of lipids drags nanosheets toward the opposite direction, and nanosheets insert into the lipid membrane. In our previous work, we found that the lipid extraction behavior depends on temperature and other factors that could lead to the phase transition of lipid membranes. Strategies to tune the lipid extraction behavior proposed in previous work could be used to prevent the formation of these destructive interaction states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation